Creating and simulating turbulence generation on NACA S1046 airfoil with CFD software - Erwin, Erwin; Muhammad Syihab, Fachry; Wiyono, Slamet; Putra, Bima Heska; Susanto, Edy; Anwar Ilmar, Ramadhan; Wan Hamzah, Wan Azmi (Akademi Baru, 2024)
The efficiency of wind turbines according to Betz limits ranges around 59%, in its development the efficiency of wind turbines is challenging to reach 50%. To increase this efficiency, many innovations were made such as the addition of tail direction, wind direction, the use of magnetic bearings, and turbulators. Flow separation that occurs in the blade causes a decrease in performance in the blade, which also occurs in vertical wind turbine blades. This research used a turbulator to reduce or shift the position of separation on the blade to improve turbine efficiency. This study aims to analyze the effectiveness of the use of turbulators to reduce or shift separation in wind turbine blades. The method used is to build a 3d model of the blade and turbulator, and perform simulations using CFD Ansys, with a steady flow with k-w Shear Stress Transport (k-w SST) turbulent model, at several speeds and angles of attack. The data taken is flow data onthe blade, drag coefficient, and lift coefficient. When a turbulator is introduced, the results show a discernible delay in flow separation on the airfoil, namely at angles of 6°, 7°, and 8° with speeds ranging from 1 to 5 m/s. Furthermore, changes in thevalues of Cl and CD are noted. Pressure distribution contours and streamlines are graphically represented alongside the current numerical values. The optimal placement for the turbulator is at 40% and 50% of the chord length, producing the greatest increase in Cl and Cl/Cd ratio in this particular version.